STABILITAS HASIL DAN ADAPTABILITAS KULTIVAR TEMBAKAU MAGETAN MENGGUNAKAN METODE EBERHART RUSSELL - Ruly Hamida; Mala Murianingrum; Djumali Djumali (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2020)
Magetan tobacco is one type of tobacco that has an important role in the kretek cigarette industry in Indonesia. Some tobacco varieties have been widely cultivated in the Magetan Regency, but the level of plant heterogeneity is quite high. The purpose of this study was to assess the yield, stability and adaptability of varieties that developed in Magetan Regency. The research material consists of 7 tobacco varieties, namely Rejeb 1, Rejeb 2, Rejeb 3, Rejeb 4, Rejeb 5, Rejeb 6, and Rejeb 7. Each variety was planted in a 12 m x 4.50 m plot with a spacing of 60 cm x 90 cm (100 plants / plot). This study used a randomized block design with three replications. The stability of the results was analyzed by the Eberhart and Russell methods. The results showed that Rejeb 4 cultivar gave the highest and stable yield of 598.89 kg / ha, higher than all cultivars tested. This is in line with the quality index and plant index values, where the Rejeb 4 variety gave the highest value in five test locations (63.65 and 38.34). Subsequently followed by cultivars Rejeb 3, Rejeb 2, and Rejeb 1 which have dynamic stability and adaptability values.